The closed method of surgical treatment of the post injection abscess of the gluteal region complicated by septic shock - Kapshitar, A. V.; Kapshitar, A. A. (Modern medical technology, 2019)
We are represent the rare clinical case of the using of a closed method for the surgical treatment of the post-injection abscess of the gluteal region, complicated by septic shock and comorbidities (diabetes Mallory’s, lung silicosis, obesity) in the volume of opening an abscess, sanitation, throughand-through drainage with polyvinylchloride drain tube through an contrapperture and primary suture of wound with following-up permanent sanitation the abscess cavity. After the elimination of the purulentnecrotic process in the primary septic focus in conjunction with the multicomponent conservative intensive therapy, it was possible to impart an abortive course to the septic process after 4 weeks with a gradual normalization of the overall clinical picture, laboratories and biochemical parameters, coagulograms. The recovery has come.